Appropriateness of antibiotic prescribing for upper respiratory tract infection in a tertiary care teaching hospital: a cross sectional study - Shah, Margi; Trivedi, Niyati A.; Chauhan, Janki (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Overuse of antibiotics among the patients with upper respiratory tract infection (URTI) is a worldwide problem, leading to antimicrobial resistance. This study is aimed to evaluate the appropriateness of the antimicrobial prescribing for upper respiratory tract infections in a tertiary care teaching hospital. Methods: This was a cross-sectional, observational study. Data was collected from outdoor adult patients who were clinically diagnosed to have URTIs from General Medicine and Otorhinolaryngology Department of a tertiary care teaching hospital. The appropriateness of antibiotics used in URTI was assessed. The data was analyzed using descriptive statistics. Results: Total 100 cases, clinically diagnosed to have URTI were included in the study. Among these, common cold (46%) and acute otitis media (23%) were the most frequent encounters. 75% of the prescriptions contained at least one antibiotic. In fact, antibiotics were the most commonly prescribed agents (21.2%) followed by antihistaminic (19.8%) and NSAIDs. 57% of the antibiotics were prescribed inappropriately, either in terms of inappropriate choice (37%) or over use (20%) of antibiotic. Conclusions: Inappropriate prescription of antibiotics for otherwise self-limiting URTI cases is a common practice even in a tertiary care teaching hospital. Implementation of multifaceted approach is needed to curtail the same.